Rotational Soft-Tissue Balance Is Highly Correlated with Rotational Kinematics in Total Knee Arthroplasty - Kinoshita, Tomofumi; Hino, Kazunori; Kutsuna, Tatsuhiko; Watamori, Kunihiko; Miura, Hiromasa (The Journal of Knee Surgery, 2021)
Recovery of normal knee kinematics is critical for improving functional outcomes and patient satisfaction after total knee arthroplasty (TKA). The kinematics pattern after TKA varies from case to case, and it remains unclear how to reproduce normal knee kinematics. The present study aimed to evaluate rotational knee kinematics and soft-tissue balance using a navigation system and to assess the influence of intraoperative soft-tissue balance on the rotational knee kinematics. We evaluated 81 osteoarthritic knees treated with TKA using a posterior stabilized (50 knees) or cruciate retaining (31 knees) prosthesis. Rotational kinematics were assessed at 0, 30, 45, 60, and 90 degrees flexion angles by using a computer-assisted navigation system. Correlation between femorotibial rotational position and measured soft tissue balance was assessed by using Spearman's rank correlation coefficient. Rotational soft-tissue balance (the median angle of rotational stress) was significantly correlated with rotational kinematics (rotational axis of the femur relative to the tibia throughout the range of motion) at all measured angles after TKA. The correlation coefficients between the median angle of rotational stress and rotational kinematics were 0.97, 0.80, 0.74, 0.71, and 0.70 at 0, 30, 45, 60, and 90 degrees of flexion, respectively (p-values <0.0001 in all measured angles). The correlation coefficient increased as the knee approached full extension. Our findings suggest that soft-tissue balance is a key factor for rotational kinematics, following both cruciate-retaining and posterior-stabilized TKA.
Keywords: total knee arthroplasty; soft tissue balance; rotational kinematics; cruciate retaining; posterior stabilized